The incidence of falls after first and second eye cataract surgery: a longitudinal cohort study. Issue 2 (15th June 2022) - Keay, Lisa; Ho, Kam Chun; Rogers, Kris; McCluskey, Peter; White, Andrew JR; Morlet, Nigel; Ng, Jonathon Q; Lamoureux, Ecosse; Pesudovs, Konrad; Stapleton, Fiona J; Boufous, Soufiane; Huang‐Lung, Jessie; et al.
Abstract: Objective: To compare fall incidence, and visual acuity and refractive status, before surgery and after first and second eye cataract surgery. Design, setting: Prospective observational study in eight tertiary referral ophthalmology clinics in public hospitals in Sydney, Melbourne, and Perth. Participants: People aged 65 years or more referred for bilateral age‐related cataract surgery during 2013–16, followed for maximum of 24 months after study entry or until six months after second eye surgery, whichever was shorter. Main outcome measures: Primary outcome: age‐ and sex‐adjusted incidence of falls. Secondary outcomes: visual acuity and refractive error. Results: The mean age of the 409 included participants was 75.4 years (SD, 5.4 years); 220 were women (54%). Age‐ and sex‐adjusted fall incidence prior to surgery was 1.17 (95% CI, 0.95–1.43) per year, 0.81 (95% CI, 0.63–1.04) per year after first eye surgery, and 0.41 (95% CI, 0.29–0.57) per year after second eye surgery. For the 118 participants who underwent second eye surgery and participated in all follow‐up visits, age‐ and sex‐adjusted incidence before (0.80 [95% CI, 0.55–1.15] falls per year) and after first eye surgery (0.81 [95% CI, 0.57–1.15] falls per year) was similar, but was lower after second eye surgery (0.32 [95% CI 0.21–0.50] falls per year). Mean habitual binocular visual acuity (logMAR) was 0.32 (SD, 0.21) before surgery, 0.15 (SD, 0.17) after first eye surgery, and 0.07 (SD, 0.15) after second eye surgery. Conclusions: First eye surgery substantially improves vision in older people with cataract, but second eye surgery is required to minimise fall incidence. Timely cataract surgery for both eyes not only optimises vision in older people with cataract, but also reduces their risk of injury from falls.